ARTIFICIAL INTELLIGENCE AND ITS ROLE IN MODERN TECHNOLOGIES - Abdugafurova Zarifa Sattarovna (Bright Mind Publishing, 2026)
Artificial intelligence (AI) is one of the most rapidly developing areas of modern science and technology. This article provides a detailed overview of AI, its basic principles, and its applications in various sectors. AI technologies are widely used in education, healthcare, industry, finance, transportation, and information technology, helping to automate routine processes, improve efficiency, and support better decision-making. In education, AI tools assist in personalized learning, student assessment, and resource management. In healthcare, AI contributes to faster diagnostics, treatment planning, and patient monitoring. Industrial applications include smart manufacturing, robotics, predictive maintenance, and process optimization. Moreover, AI is transforming business analytics, enhancing cybersecurity, and enabling innovative solutions in smart cities and sustainable development. The article also discusses the challenges associated with AI implementation, including ethical considerations, data privacy, and the need for continuous development of AI literacy among professionals. Finally, the paper highlights future trends in AI, such as the integration of machine learning, natural language processing, and computer vision, emphasizing that AI will play a critical role in shaping the technological landscape of the 21st century.
Keywords: Artificial Intelligence, Modern Technologies, Automation, Efficiency, Machine Learning, Information Technology, Education, Healthcare, Industry, Robotics, Future Trends, Ethics, Smart Systems.